Influence of menopause on chemotherapy‐induced nausea and vomiting in highly emetogenic chemotherapy for breast cancer: A retrospective observational study - Takashi Yokokawa; Kenichi Suzuki; Daiki Tsuji; Mari Hosonaga; Kazuo Kobayashi; Kazuyoshi Kawakami; Hitoshi Kawazoe; Tomonori Nakamura; Wataru Suzuki; Takahito Sugisaki; Takeshi Aoyama; Koki Hashimoto; et al. (Cancer Medicine, 2023)
Abstract Background Female sex and younger age are reported risk factors for chemotherapy‐induced nausea and vomiting (CINV) in highly emetogenic chemotherapy, but the underlying mechanism has not been elucidated. The purpose of this study was to clarify the impact of menopause on CINV. Methods This retrospective observational study analyzed data from consecutive patients who received their first cycle of perioperative anthracycline‐based chemotherapy for breast cancer between January 2018 and June 2020. The endpoints were association between CINV (vomiting, ≥Grade 2 nausea, complete response [CR] failure) and menopause as well as the association between CINV and follicle‐stimulating hormone [FSH]/estradiol [E2]. Results Data for 639 patients were analyzed. Among these patients, 109 (17.1%) received olanzapine (four antiemetic combinations) and 530 (82.9%) did not (three antiemetic combinations). Premenopausal state (amenorrhea lasting ≥12 months) was significantly associated with ≥Grade 2 nausea and CR failure in univariate analysis but not in multivariate analysis. The premenopausal FSH/E2 group (defined by serum levels; FSH <40 mIU/mL and E2 ≥20 pg/mL) had a significantly higher rate of ≥Grade 2 nausea than the postmenopausal FSH/E2 group (FSH ≥40 mIU/mL and E2 <20 pg/mL) (48.8% vs. 18.8%, p = 0.023). Conclusions Our results suggest that changes in FSH and E2 due to menopause may affect the severity of nausea and that FSH and E2 (especially FSH) levels might be useful indicators for CINV risk assessment.